Empyema: An Increasing Concern in Canada - Christian Finley; Joanne Clifton; J Mark FitzGerald; John Yee (Canadian Respiratory Journal)
BACKGROUND: Empyema is a suppurative infection of the pleural space. Without prompt treatment, it can result in significant hospital stays, more invasive treatments as it progresses, and substantial morbidity and mortality.